Third-party impacts of short-term rental accommodation: a community survey to inform government responses. Issue 5 (4th May 2022) - Muschter, Sabine; Caldicott, Rodney W.; von der Heidt, Tania; Che, Deborah
Abstract: Short-term rental accommodation (STRA) sharing economy platforms, such as Airbnb, give rise to externalities or negative third-party impacts in neighbourhoods. Governments worldwide continue to grapple with how to best regulate STRA platforms given such externalities, especially in the wake of COVID-19. When STRA is perceived as poorly controlled, anecdotal reports indicate that community resentment around perceived inequities and negative economic, social, and environmental impacts rise. However, little research has systematically investigated community perceptions of STRA, notably Airbnb effects at a local, non-metropolitan level, as well as preferred regulatory responses. This paper examines such community perceptions in one of Australia's top tourism destinations, the Byron Shire. An online survey of 819 residents, identified four positive, eight negative and seven mixed impacts of Airbnb on community. To redress the adverse effects and enhance the sustainable performance of STRA (including Airbnb), a majority of residents favoured several regulatory strategies such as mandatory on-site management of STRA properties and better avenues to report complaints of misconduct. However, with notable reported differences between host and non-host residents. The study thus offers possible regulatory options to support regionally-based local councils as they seek to address opposing community concerns.